Theoretical and Computational Methods in Mineral Physics Geophysical Applications. - Wentzcovitch, Renata M. (Reviews in Mineralogy and Geochemistry Ser., 2018)
Reviews in Mineralogy & Geochemistry (RiMG) volumes contain concise advances in theoretical and/or applied mineralogy, crystallography, petrology, and geochemistry.